2019
DOI: 10.1088/1361-6528/aaf7cc
|View full text |Cite
|
Sign up to set email alerts
|

Polymer spreading on substrates with nanoscale grooves using molecular dynamics

Abstract: Understanding how liquid polymer interacts with and spreads on surfaces with nanoscale texture features is crucial for designing complex nanoscale systems. We use molecular dynamics to simulate different types of polymer as they spread on substrates with a single nanoscale groove. We study how groove design affects the potential energy of a substrate and how this governs polymer spreading and orientation. Based on our simulations, we show that groove shape, polymer chemistry, and polymer molecule entanglement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…The polymer spreads in a single groove and d ⊥ is unaffected by the texture, as we have previously reported in detail. 15 Figure S2 illustrates the number of grooves and peaks the polymer encounters during spreading on several example substrates. However, although perpendicular spreading depends on the number of grooves the polymer encounters, the groove shape is the dominant factor that determines anisotropic polymer spreading.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The polymer spreads in a single groove and d ⊥ is unaffected by the texture, as we have previously reported in detail. 15 Figure S2 illustrates the number of grooves and peaks the polymer encounters during spreading on several example substrates. However, although perpendicular spreading depends on the number of grooves the polymer encounters, the groove shape is the dominant factor that determines anisotropic polymer spreading.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The bead mass is 0.2 kg/mol; thus, the molecular weight is 2 kg/mol. The potential function interactions that define the system are similar to validated potentials used in previous research and are discussed in detail in the Supporting Information (SI). , , Gravity is negligible at this scale and, therefore, not included in our model.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are many studies on surface wetting with different surface textures by molecular dynamics simulation because of its convenience and accuracy. Noble et al studied the spreading behaviors of polymer on a substrate with a single groove and found that groove shape is one of the most important factors that determines the spreading behaviors of polymer. The transition between Wenzel state and Cassie state of droplets on a rough surface is studied by Koishi et al; the height of nanopillars and the spacing between nanopillars have a great impact on the transition between Wenzel state and Cassie state, and the free-energy barrier between the Wenzel state and Cassie state becomes higher with higher nanopillars.…”
Section: Introductionmentioning
confidence: 99%